2018
DOI: 10.1093/ajh/hpy128
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Central Aortic Blood Pressure in Youth: Role of Obesity and Sex

Abstract: In a cohort of youth with a wide range of adiposity levels, central aortic BP was elevated among individuals with SO and associated with BMI but not body fatness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Weight is a significant predictor of PWV ( p < 0.0001), SBP ( p < 0.0001), cSBP ( p < 0.0001), cDBP ( p < 0.0001) and cPP (p = 0.0117). However, central BP values are not well-validated with regard to normal ranges in children, and questions are raised with regard to the possibility of tonometry and oscillometry underestimating central BP [ 40 , 41 ], thus making the use of these methods of measurement questionable with regard to their clinical use. Our results, nevertheless, show strong positive correlations between central BP values and BMI, which suggests that even if the values are underestimated, adipose tissue still has an impact on central BP.…”
Section: Discussionmentioning
confidence: 99%
“…Weight is a significant predictor of PWV ( p < 0.0001), SBP ( p < 0.0001), cSBP ( p < 0.0001), cDBP ( p < 0.0001) and cPP (p = 0.0117). However, central BP values are not well-validated with regard to normal ranges in children, and questions are raised with regard to the possibility of tonometry and oscillometry underestimating central BP [ 40 , 41 ], thus making the use of these methods of measurement questionable with regard to their clinical use. Our results, nevertheless, show strong positive correlations between central BP values and BMI, which suggests that even if the values are underestimated, adipose tissue still has an impact on central BP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both weight and height are significantly correlated to most PWA parameters; hence we can affirm that the correlations between the BMI and the PWA parameters are accurate. Some studies suggest that central BP values acquired through tonometry and oscillometry devices may be underestimated [55,56]; however, normal ranges of the central BP values in children are not entirely supported. This study showed a strong positive link between the BMI and cSBP, and cDBP, respectively, meaning that excess weight is associated with higher central BP values.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that microparticles and EMPs levels are higher in youth with higher adiposity level is congruent with many other biomarkers of CVD risk, including other markers of subclinical endothelial dysfunction. 14 , 27 , 28 , 29 , 30 There are a number of reasons for the underlying association between adiposity and microparticle/EMP levels, including higher inflammation, dysregulated coagulation, and the independent role obesity may have on nitric oxide availability through a cascade of events. 10 , 31 , 32 , 33 However, this study does not provide the evidence for a causal link, and the underlying cause requires further investigation.…”
Section: Discussionmentioning
confidence: 99%